The Role of Exercise and Mitochondrial Biogenesis in Aging Process - Nasihun, Taufiqurrachman (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2018)
Aging can be defined as the progressive accumulation of changes with time associated with increasing vulnerability to disease and death which accompanies advancing age. The time related changes are attributed to the aging process (Harman, 1981). There are growing evidences that a number of the detrimental free radicals reactions are continuously occur throughout the cells of the body constituting the prominent contributor to aging process (Harman, 1981). This theory was extended to mitochondrial theory of aging, suggesting that mitochondria as the main source and target of reactive oxygen species (ROS) produced in association with aging processes and degenerative diseases (Payne and Chinnery, 2015). Mitochondria has a pivotal roles in multiple cellular processes such as oxidative phosphorylation (OXPHOS), apoptosis, b-oxidation of fatty acids, steroid biosynthesis, calcium homeostasis, intermediary metabolism, and cell signaling (Yin and Cadenas, 2015). Recent studies indicated that oxidative damage due to accumulation of ROS result from mitochondria production were associated with multiple pathologies, including neurodegenerative diseases, diabetes, cancer, and premature aging (Cedikova et al., 2016).Â